1995
DOI: 10.1007/bf00020221
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the signal recognition particle (SRP) RNA population of tomato (Lycopersicon esculentum)

Abstract: Molecular cloning of 30 cDNAs and subsequent characterization of the corresponding SRP RNA from four cultivars of tomato (Lycopersicon esculentum) revealed altogether 14 sequence variants, which could be ordered into six groups. The expression of five representatives from these groups was examined by reverse transcriptase-polymerase chain reaction (RT-PCR) in different cultivars and different tissues. Although one cultivar-specific SRP RNA variant could be detected in the leaf SRP RNA population, identical SRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…Our previous analysis of several SRP RNA sequence variants from tomato has indicated that at least ten different SRP RNA genes are present in the tomato genome [42]. This assumption could now be confirmed by Southern analysis (Fig.…”
Section: Restriction Analysand Of Tomato Genomic Dnasupporting
confidence: 54%
See 4 more Smart Citations
“…Our previous analysis of several SRP RNA sequence variants from tomato has indicated that at least ten different SRP RNA genes are present in the tomato genome [42]. This assumption could now be confirmed by Southern analysis (Fig.…”
Section: Restriction Analysand Of Tomato Genomic Dnasupporting
confidence: 54%
“…In this work, Mtlhlbach and Sanger [34] demonstrated the resistance of 7S RNA transcription to c~-amanitin. Additional support was provided by our results from direct sequencing of the tomato SRP RNA [18] and recently of fulllength cDNAs [42]. All sequence variants possess three to five uridines at the very 3'-end which points to the pol Ill-specific transcription termination within DNA-stretches of thymidine residues [ 15].…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations